Lena Smart Pillow / Nur Hafizah Ali, Ahmad Mustaqim Naim Abdul Ghafar ... [et al.] - Ali, Nur Hafizah; Abdul Ghafar, Ahmad Mustaqim Naim; Abdul Zaman, Muhammad Aminuddin Sz; Jamil, Mohamad Ilman; Mat Ahan, Mohd Fadzil (2019)
Mawadah Sdn Bhd is a company strive to make the world healthier through their sleep and more sustainable through innovation. Our team has invented the Lena Smart Pillow comes with Technology features that has been proven through our research to help people with insomnia or sleeping problem. The Lena Smart Pillow operates on the natural principle of 'bone conduction. It triggers your body's relaxation response, the parasympathetic nervous system. It is equally effective for all ages, and particularly helpful for those experiencing stress, anxiety, sleep disturbances. Other than that, our company also targets the group that facing the sleeping problem such as insomnia, snoring, neck pain. Our Product Lena Smart Pillow is using differentiation as sustainable competitive advantages. We try to look for competitor product, highlight their mistake and improve it, this will ensure our company will not having the same mistake. The target market group that Mawadah Sdn Bhd target is the middle income group, because the group of people has great potential. Besides that, our company will collaborate with some company which these companies serve as the constant supplier for Smart Lena Pillow. Lastly Smart Lena Pillow will also collaborate with expert and doctor to create the pillow that will help improve sleeping quality.•%